Being and planning, world formation and authenticity in Heideggerian analysis. (August 2018) - Low, Nicholas; Sturup, Sophie
The theory of being helps us understand the condition of planning in an evanescent, shape-shifting world and how to be a strategic planner in such a world. Martin Heidegger's investigation of being reveals important and sometimes disconcerting insights into humans and the worlds they inhabit and generate. In this article, we use Heidegger's framework of thought to reveal what being means for planners and planning. In our investigation, we focus on one theme that seems fundamental to the practice of planning, the transformative impulse, and we reflect on how Heidegger's thought provides insights into that element. We show how Heidegger, the philosopher of the everyday, overturned the Cartesian dualistic ontology of subject–object, replacing it with the holistic being-in-the-world. We explore how this holistic ontology helps reinterpret transformative practice. We argue that effective transformation of society involves a transformation of being.